Diabetes mellitus em portadores de cirrose: prevalência e impacto prognóstico - Carmo, Luiza Fabres do [UNIFESP] (2018)
Introduction: Type 2 diabetes mellitus (DM) has been identified is 20 to 60% of patients with cirrhosis and has been associated with poor outcomes in cirrhosis, coursing with higher mortality from liver failure, increased risk of decompensation and increased incidence and mortality due to hepatocellular carcinoma (HCC). The impact of the presence of DM in cirrhotic patients has been evaluated in few studies, mainly with selected subjects, which hampers the applicability of their findings. Objectives: To identify the prevalence of DM in cirrhotic patients; the influence of diabetes on the functional status of cirrhosis and analyze the impact of DM on the natural history of liver cirrhosis. Methods: Observational crosssectional analytical study performed by reviewing of standardized medical records of cirrhotics from any etiology, followed in an outpatient clinic from a single referral center in Hepatology, between January 1986 and June 2014. Results: 303 patients were selected, with mean age of 54,6 ± 11,5 years, with male predominance (68,6%). Ninety eight subjects (32.3%) were diabetic on admission. DM was more prevalent among Child A patients than in those Child B or C (37.2% vs. 24.8%, respectively, p = 0.022); likewise, DM was more common in subjects with MELD <10, as compared to those with MELD score between 1014 and ≥ 15 (42.9%, 29.8% and 22.2%, in this order, p = 0.011). In a logistic regression model, over a 10year followup, DM was considered an independent risk factor for death or liver transplantation (odds ratio (OR): 1.52; 95% confidence interval (CI): 1.032.24; p = 0.035), hepatic decompensations (OR: 3.93, 95% CI: 1.808.56, p = 0.001) and HCC (OR: 4.43, 95% CI: 1.6611.85; p = 0.003). Conclusion: DM was very prevalent among cirrhotic patients, particularly amog those with compensated disease, and was associated with increased mortality and higher incidence of major complications of cirrhosis. Therefore, more attention should be paid to early diagnosis and adequate management of glucose disorders in these patients.